2018
DOI: 10.1016/j.ijbiomac.2017.11.088
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of glycolipopeptide cell-bound biosurfactants against skin pathogens

Abstract: The antimicrobial and anti-adhesive activities of the cell-bound biosurfactants, produced by Lactobacillus pentosus (PEB), characterized as glycolipopeptide macromolecules, were evaluated against several microorganisms present in the skin microflora, envisaging its potential use as a "natural" ingredient in cosmetic and personal care formulations. Their performance was compared with another cell-bound biosurfactants also characterized as glycolipopeptides produced by Lactobacillus paracasei (PAB). At concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 33 publications
5
37
0
1
Order By: Relevance
“…Our results are in accordance with those of Vecino et al ( 2018 ) who reported that the pre-treatment of a polystyrene surface with biosurfactants produced by Lactobacillus pentosus and Lactobacillus paracasei inhibited bacterial and C. albicans adhesion by 30–81%. In another study, Gudiña et al ( 2010b ) reported that the highest antiadhesive activity of the biosurfactant produced by L. paracasei was observed against Staphylococcus aureus (72.0%) and S. epidermidis (62.1%) at a concentration of 25 mg mL −1 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in accordance with those of Vecino et al ( 2018 ) who reported that the pre-treatment of a polystyrene surface with biosurfactants produced by Lactobacillus pentosus and Lactobacillus paracasei inhibited bacterial and C. albicans adhesion by 30–81%. In another study, Gudiña et al ( 2010b ) reported that the highest antiadhesive activity of the biosurfactant produced by L. paracasei was observed against Staphylococcus aureus (72.0%) and S. epidermidis (62.1%) at a concentration of 25 mg mL −1 .…”
Section: Resultssupporting
confidence: 93%
“…Also, we have shown that biosurfactants have strong antiadhesive activities against bacterial and yeast strains on a polystyrene surface (Janek et al, 2013b ). Vecino et al ( 2018 ) have reported significant antiadhesive properties of glycolipopeptide cell-bound biosurfactants against all of the tested microorganisms, except E. coli and C. albicans (<30% antiadhesive activity). Although there are a few intensive studies on the antimicrobial and antiadhesive activities of biosurfactants, much work is still needed to understand the mechanism of action of the surface-active compounds.…”
Section: Introductionmentioning
confidence: 98%
“…Vecino et al . () investigated the antimicrobial and anti‐adhesive properties of cell‐bound biosurfactants produced by Lactobacillus pentosus (PEB), which are characterized as glycolipid molecules against several micro‐organisms found amongst human skin flora. The performance of PEB was compared against the glycolipids produced by Lactobacillus paracasei (PAB).…”
Section: Health‐related Applicationsmentioning
confidence: 99%
“…While the majority of biosurfactant-related work is focussed on biosurfactants that are produced extracellularly by micro-organisms much less work has been carried out on cell-bound biosurfactants many of which are produced by, for example, probiotic Lactobacilli strains which have the added advantage of being nontoxic, biodegradable and environmentally friendly (Satpute et al 2016b). Vecino et al (2018) investigated the antimicrobial and anti-adhesive properties of cell-bound biosurfactants produced by Lactobacillus pentosus (PEB), which are characterized as glycolipid molecules against several micro-organisms found amongst human skin flora. The performance of PEB was compared against the glycolipids produced by Lactobacillus paracasei (PAB).…”
Section: Dermatological Applicationsmentioning
confidence: 99%
“…However, very limited research exists regarding the application of biosurfactants in the pharmaceutical industry. Related to the applications of biosurfactants in these two last areas, some researchers have observed an antimicrobial activity of several biosurfactants against pathogenic strains [9][10][11]. Additionally, researchers have discovered that a biosurfactant obtained from corn steep liquor (CSL) exhibits sunscreen protective properties [12].…”
Section: Introductionmentioning
confidence: 99%